Recasting conservatism : Oakeshott, Strauss, and the response to postmodernism - Devigne, Robert (Yale University Press, 1994)
A new conservative theory in Britain and America has altered the terms of political debate, not only among conservatives, but also among liberals, social democrats, and socialists. In this book, Robert Devigne explores how this conservative thought - in particular the work of the British political philosopher Michael Oakeshott, the American Leo Strauss, and their followers - is responding to the challenge of postmodernism, to the pervasive loss of civil traditions, morality, and authority in contemporary societies. Devigne argues persuasively that new British and American conservative theories are not merely variants of economic liberalism, but also embody a search for new authoritative political and civil relations, each attempting to modify society's future course with outlooks significantly different from those of their conservative predecessors. He shows that while both theories are responding to similar political problematics, their origins in different political philosophies have contributed to distinct constitutional doctrines and political objectives. Devigne explains how these separate outlooks and goals are rooted in different views on morality, authority, democracy, liberty, justice, community, and religion, and in distinct preferences toward economic, social, and foreign policy. Throughout the book, Devigne situates the theories among the central debates of political philosophy and compares each theory to dominant British and American political outlooks of the past.